2013
DOI: 10.1001/jama.2013.8272
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Differences in Survival Among Black and White Women With Breast Cancer

Abstract: In the SEER-Medicare database, differences in breast cancer survival between black and white women did not substantially change among women diagnosed between 1991 and 2005. These differences in survival appear primarily related to presentation characteristics at diagnosis rather than treatment differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
238
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(254 citation statements)
references
References 59 publications
14
238
1
1
Order By: Relevance
“…The current study has extended previous research for Brazil in showing that age is an independent predictor of cause-specific mortality, at least in the presence of the numerous control variables available for our analysis. Of course, survival differentials by age may depend on a variety of other key factors not included in our models such as the socioeconomic status of patients 30 , access to health care 31,32 , and more detailed data on types of treatment employed 12,17,41,42 , which reinforces the need for further analysis. Understanding the pathways linking age to mortality due to breast cancer should help doctors, epidemiologists and policy makers to propose specific measures to improve the chances of survival for women of different age groups, particularly in a context of profound changes in the population age structure.…”
Section: Discussionmentioning
confidence: 97%
“…The current study has extended previous research for Brazil in showing that age is an independent predictor of cause-specific mortality, at least in the presence of the numerous control variables available for our analysis. Of course, survival differentials by age may depend on a variety of other key factors not included in our models such as the socioeconomic status of patients 30 , access to health care 31,32 , and more detailed data on types of treatment employed 12,17,41,42 , which reinforces the need for further analysis. Understanding the pathways linking age to mortality due to breast cancer should help doctors, epidemiologists and policy makers to propose specific measures to improve the chances of survival for women of different age groups, particularly in a context of profound changes in the population age structure.…”
Section: Discussionmentioning
confidence: 97%
“…This association was not found in a hospital-based cohort in São Paulo with 430 women diagnosed in 1999/2000 38 ; on the other hand, a study made with 30,293 women with breast cancer diagnosed between 2003 and 2008, and identified in a population-based cancer registry in the city of São Paulo showed significant association between black race/ethnicity and shorter survival 39 ; another historic cohort study conducted in Florianópolis with 1,002 women diagnosed between 2000 and 2002 showed an association between Caucasian race/white skin color and longer survival which remained after school-education adjustment, but not after staging adjustment 23 . Many studies conducted in the USA also showed an association between race/skin color and better prognosis, a number of them even after being adjusted for socioeconomic status and staging 34,40,41,42 . In Europe, studies that consider socioeconomic status are more frequent than those that investigate race/ skin color as determinants of diseases, but Jack et al 43 found shorter survival in black women, even after adjustment for other medical and social variables.…”
Section: Discussionmentioning
confidence: 99%
“…3 The effectiveness of breast cancer prevention and early detection strategies depends in part on the ability to accurately identify individuals at increased risk of breast cancer. Models for predicting the absolute risk of breast cancer have been used for chemoprevention decision making and for determining eligibility for recruitment into prevention trials.…”
Section: Introductionmentioning
confidence: 99%